FEATURES OF RHEUMATIC DISEASES IN ELDERLY PATIENTS WITH DIABETES MELLITUS - Bafayev J. T. (Web of Journals Publishing, 2025)
This article examines the features of the course of rheumatic diseases in elderly patients with diabetes mellitus (DM). The issues of epidemiology, pathophysiological mechanisms of the relationship between these two conditions, clinical manifestations and treatment methods are considered. Particular attention is paid to the importance of an individual and comprehensive approach to therapy, as well as the prevention of possible complications. Current information on the impact of systemic inflammatory processes, elevated uric acid levels and vascular changes on the development of rheumatic pathologies in individuals with DM is provided. The conclusion emphasizes the need for additional research to improve the quality of life of such patients.
Keywords: Rheumatic diseases, diabetes mellitus, old age, comorbidity, osteoarthritis, gout, treatment, systemic inflammation